THE EFFECT OF IMITATION MODEL TECHNIQUE AND LITERARY READING INTEREST TO SHORT STORIES WRITING SKILL - Vitta Jamil; Syahrul Ramadhan; Yasnur Asri (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2018)
This study aims to describe effect of short story writing skills using model imitation techniques and literary reading interest with conventional techniques in class IX of SMP Negeri 2 Pariaman. This type of research is quantitative with factorial 2x2 design. Sampling was done by purposive sampling. Research variables were independent variables, dependent variables, and moderator variables. The research instruments were questionnaires and performance tests. The data in this study were scores on the results of short story writing skills tests. The research procedure consists of the preparation stage, the implementation phase, the assessment stage. The results of this study are as follows. First, the value of short story writing skills of students taught using model imitation techniques is higher than the value of students taught by conventional techniques. Second, the value of short story writing skills of students who have a high literacy interest, who are taught using model imitation techniques, is higher than high literary reading interests taught using conventional techniques. Third, the value of short story writing skills of students who have low literary interest, who are taught using model imitation techniques, is higher than the low literary reading interest taught by conventional techniques. Fourth, there is an interaction between literary interest in reading and imitation techniques in influencing students' short story writing skills.Keyword: effect, short stories, imitate model technique, Interest in literature  reading.PENGARUH TEKNIK TIRU MODEL DAN MINAT BACA SASTRA TERHADAP KETERAMPILAN MENULIS CERPEN  AbstrakPenelitian ini bertujuan untuk mendeskripsikan dampak hasil belajar keterampilan menulis cerpen dengan menggunakan teknik tiru model dan minat baca sastra dengan teknik konvensional di kelas IX SMP Negeri 2 Pariaman. Jenis penelitian ini adalah kuantitatif dengan desain factorial 2x2. Pengambilan sampel dilakukan dengan cara purposive sampling. Variabel penelitian yaitu variabel bebas, variabel terikat, dan variabel moderator. Instrumen penelitian adalah angket dan tes unjuk kerja. Data dalam penelitian ini adalah skor hasil tes keterampilan menulis cerpen. Prosedur penelitian terdiri dari tahap persiapan, tahap pelaksanaan, tahap penilaian. Hasil penelitian ini sebagai berikut. Pertama, nilai keterampilan menulis cerpen siswa yang diajar menggunakan teknik tiru model lebih tinggi daripada nilai siswa yang diajar dengan teknik konvensional. Kedua, nilai keterampilan menulis cerpen siswa yang memiliki minat baca sastra tinggi, yang diajar menggunakan teknik tiru model, lebih tinggi daripada minat baca sastra tinggi yang diajar menggunakan teknik konvensional. Ketiga, nilai keterampilan menulis cerpen siswa yang memiliki minat baca sastra rendah, yang diajar menggunakan teknik tiru model, lebih tinggi daripada minat baca sastra rendah yang diajar menggunakan teknik konvensional. Keempat, terdapat interaksi antara minat baca sastra dengan teknik tiru model dalam mempengaruhi keterampilan menulis cerpen siswa.Kata Kunci: pengaruh, cerpen, teknik tiru model, minat baca sastra.